Grotesque representations of deviant sexuality in Ian McEwan's selected short stories - Moghadam, Nahid Shahbazi; Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2013)
Themes of sexuality, particularly in excessive and extraordinary forms, can readily merge into the grotesque to ameliorate their depiction and thematic impact. Ian McEwan’s early fiction best exemplifies such inclinations. The psychologically violent and excessive world of McEwan’s early fiction is basically conceived in the milieu of sex and through grotesque representations. In this relation, the present work selectively focuses on “Solid Geometry” from First Love, last Rites (1975) and “Reflections of a kept Ape” and “Dead as they Come” from In between the Sheets (1978) to illustrate the implication and range of the grotesque in McEwan’s short fiction. The selected stories are discussed for their portrayal of the grotesque, as represented through transgressive partnership and deviant sexuality. The portrayal of sexuality in McEwan’s early short fiction offers a variety of the grotesque types of narrative mingling the mode both with the fantastic and the caricature.